2012
DOI: 10.1073/pnas.1200791109
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial swimmers that infiltrate and take over the biofilm matrix

Abstract: Bacteria grow in either planktonic form or as biofilms, which are attached to either inert or biological surfaces. Both growth forms are highly relevant states in nature and of paramount scientific focus. However, interchanges between bacteria in these two states have been little explored. We discovered that a subpopulation of planktonic bacilli is propelled by flagella to tunnel deep within a biofilm structure. Swimmers create transient pores that increase macromolecular transfer within the biofilm. Irrigatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
149
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(153 citation statements)
references
References 34 publications
2
149
0
1
Order By: Relevance
“…This ecological interpretation is consistent with recent studies suggesting that bacterial phenotypes as fundamental as cell shape contribute to optimizing surface occupation (Persat et al, 2014), that competing strains attempt to displace one another from occupied substrata (Nadell and Bassler, 2011;Houry et al, 2012;Schluter et al, 2015), and that cell lineages vie for access to areas harboring the highest nutrient concentrations within biofilms (Xavier and Foster, 2007;Nadell et al, 2008;Kim et al, 2014). A recent report further supports the generality and ecological realism of our results.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This ecological interpretation is consistent with recent studies suggesting that bacterial phenotypes as fundamental as cell shape contribute to optimizing surface occupation (Persat et al, 2014), that competing strains attempt to displace one another from occupied substrata (Nadell and Bassler, 2011;Houry et al, 2012;Schluter et al, 2015), and that cell lineages vie for access to areas harboring the highest nutrient concentrations within biofilms (Xavier and Foster, 2007;Nadell et al, 2008;Kim et al, 2014). A recent report further supports the generality and ecological realism of our results.…”
Section: Discussionsupporting
confidence: 80%
“…Previous work suggests that invasion into the interior of a resident biofilm is indeed a competitive strategy employed by planktonic bacteria: several species of Bacillus invade both con-and heterospecific biofilms by tunneling to the interior using flagellar-mediated motility (Houry et al, 2012). The biofilm interior is not always expected to represent favorable niche space, for example, when the bottom layers become oxygen-or nutrient-limited.…”
Section: Discussionmentioning
confidence: 99%
“…Biofilm bacteria are usually depicted as being sessile and entrapped within an extracellular matrix, remaining nonmotile and in a unique state of growth (2). In PNAS, the work by Houry et al (3) challenges this view of biofilm bacteria with the discovery that a subpopulation consisting of 0.1-1% of cells within a biofilm, referred to as stealth swimmers, has the ability to remain motile. Previous work has shown a role for motility in the initial attachment to surfaces, the construction of 3D structures, and the final step of biofilm disassembly (4).…”
mentioning
confidence: 98%
“…Biofilms are known to evolve over time and change matrix composition (6), and the altered resistance to swimmer penetration reinforces the fact that biofilms are not static entities. The work by Houry et al (3) observes that changing viscoelastic properties in older biofilms because of increased levels of exopolysaccharide results in attenuated permeability to swimmer cells. It is also observed that the tunneling ability is not intrinsic to all motile bacteria, suggesting that the strength of an organism's motility or some other unique structural feature of these biofilms could limit stealth swimmer activity.…”
mentioning
confidence: 99%
“…The interactions between the microbes and the surface influence initial biofilm formation and generate adhesive complexes that need to be overcome or dismantled prior to large-scale motion or detachment [85,96], but this important topic is simply too extensive to cover here. In addition, self-propelled bacterial swimmers are most commonly associated with the planktonic phenotype but are known to arise in some biofilms, both early stage and mature [45,76], and could potentially be tractable to the analytical tools of active matter currently undergoing vigorous investigation [57], but since their relationship with biofilm mechanics has not been explored they will not be discussed further. The coupling between mechanics and community dynamics is likely to be of key importance in the future and is discussed in §4.…”
Section: Introductionmentioning
confidence: 99%